Podcast As An Affective Democratic Space: Political Framing and Youth Engagement in Mojok.Co's Putcast - Subkhi Ridho; Lala Affafa (Universitas Negeri Yogyakarta, 2025)
The rise of digital media has profoundly reshaped how Indonesian citizens engage in political discourse. This study explores how Mojok.co's Putcast functions as an affective democratic space and a medium of political education for young audiences. Employing a qualitative approach that combines content analysis, grounded theory, and in-depth interviews with the editorial team, this research analyzes two podcast episodes: